Factors Related To Stunting Events In Body 25 - 59 Months At Tanjung Wangi Village, Pataruman Health Center Working Area, West Bandung Regency In 2019 - B Budiman; Teguh Akbar Budiana; Laras Pualamsari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
This study talks about stunting, that is, a chronic malnutrition problem that occurs as the fetus is still in the womb and only appears after the child has been two years old. West Bandung Regency is one of the priority districts has determined 10 villages in focusing (locus) to handle stunting cases, like at Tanjung Wangi Village. The research design used a case control. The sample was toddlers aged 25 - 59 months who were selected by purposive technique. Respondents were taken from 30 case samples and 30 control samples from the results of questionnaire, interviews, the SQFFQ form and height measurements using microtoise. Data analysis included univariate and bivariate analysis using the chi square test. The results of this study showed that there was no relationship among protein intake and stunting, calcium intake (p = 0.670), health insurance ownership status (p = 0.335), history of ANC (p = 0.515) and maternal occupation (p = 0.859). ) with the stunting event. However, there was a relationship between vitamin D intake (p = 0.022) and body length at birth (p = 0.021) with the incidence of stunting.